2015
DOI: 10.4028/www.scientific.net/amr.1129.573
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Fly Ash Geopolymeric Mortar for Coating of Ordinary Portland Cement Concrete Exposed to Harsh Chemical Environments

Abstract: Premature degradation of ordinary Portland cement (OPC) concrete infrastructures is a current and serious problem with overwhelming costs amounting to several trillion dollars. The use of concrete surface treatments with waterproofing materials to prevent the access of aggressive substances is an important way of enhancing concrete durability. The most common surface treatments use polymeric resins based on epoxy, silicone (siloxane), acrylics, polyurethanes or polymethacrylate. However, epoxy resins have low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…133 Recently, Tahri et al investigated the resistance to chemical attack (by sulfuric and nitric acid) of fly ash geopolymers for coating portland cement concrete. 134 It has been found that the fly ash geopolymeric mortar shows a good performance for sulfuric acid concentrations of both 10% and 20%. Even for a sulfuric acid concentration of 30%, this mortar shows good acid resistance for immersion for 14 days.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…133 Recently, Tahri et al investigated the resistance to chemical attack (by sulfuric and nitric acid) of fly ash geopolymers for coating portland cement concrete. 134 It has been found that the fly ash geopolymeric mortar shows a good performance for sulfuric acid concentrations of both 10% and 20%. Even for a sulfuric acid concentration of 30%, this mortar shows good acid resistance for immersion for 14 days.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…This material is inorganic polymer with lower CO 2 footprint. It is produced from a large number of natural minerals [56,57] or industrial waste [12][13][14][15]18,25,33,56,58] activated by an alkaline solution at ambient or slightly high temperature. It presents sometimes problems of cost and durability [59].…”
Section: Introductionmentioning
confidence: 99%